Rock Slopes Stability Analysis along the Road of (Al-Rabban Hormizd) Monastery in Alqosh Anticline, Northern Iraq (Iraqi National Journal of Earth Science (INJES), 2026)
The aims of the current study include slope stability analysis conducted by kinematic analysis and Slope Mass Rating (SMR) at six selected stations on the road to (Al-Rabban Hormizd) Monastery located at Alqosh anticline, northern Iraq. The current study shows that station (1) has the possibility of two cases of direct toppling by intersection (J1) with both bedding plane (So) and (J3), both of which are stable conditions. Station (2) shows two possible cases: planner sliding on (J2), which is a bad and unstable condition. The second possible case is direct toppling from the intersection of (J1) with (J3), which is a good and stable condition. Station (3) shows two possible cases; the first is the planner sliding of (J2) with an (SMR) value of (23), so it is bad and unstable. The second is the wedge sliding from the intersection of (J2 with J3), which is a good and stable. At station (4), three possible failure cases appeared. The first is planner sliding on (J1), which is bad and unstable. The second possible case is the wedge sliding from the intersection of (J1) with both (J2 and J3), and in both cases the (SMR) value is (65), so they are both good and stable cases. The third possible case is the direct toppling from the intersection of (J2 with J3), which is normal and partially stable. Station (5) shows two cases; first is a wedge sliding from the intersection (J1 with J2), which is good and stable; second is a flexural toppling on (J3), which is normal and partially stable. Station (6) shows two cases; first is a planer sliding on (J3) with an (SMR) value of (13), which is very bad and completely unstable, and requires support by (Re-excavation Walls); second possible case is a wedge sliding from the intersection (J3) with both (J1 and J2), both are normal and partially stable.
Keywords: Rabban Hormizd, Kinematic analysis, support types.